2002
DOI: 10.1002/app.11062
|View full text |Cite
|
Sign up to set email alerts
|

Gelatin/montmorillonite hybrid nanocomposite. I. Preparation and properties

Abstract: Gelatin/montmorillonite (MMT) hybrid nanocomposite was directly prepared with unmodified MMT and gelatin aqueous solution. Thermal and mechanical properties of the composite were investigated by differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), scanning electron microscopy (SEM), and tensile tests. The results indicated that an intercalated or partially exfoliated nanocomposite could be achieved, and the properties of the composite were significantly improved. A T g peak of high temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
95
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(108 citation statements)
references
References 20 publications
9
95
0
4
Order By: Relevance
“…The degradation temperatures of the films agree with the findings of Zhong and Li [15] and Sanyang et al [32] who reported the degradation temperature of glycerol-rich phase of kudzu starch-based edible films and biodegradable films based on sugar palm starch between 150°C to 280°C and 120°C to 290°C, respectively. Further heating beyond 260°C induced the highest thermal degradation rate which is reflected by the sharp weight reduction of the films.…”
Section: Thermal Stability Of the Filmsupporting
confidence: 88%
See 2 more Smart Citations
“…The degradation temperatures of the films agree with the findings of Zhong and Li [15] and Sanyang et al [32] who reported the degradation temperature of glycerol-rich phase of kudzu starch-based edible films and biodegradable films based on sugar palm starch between 150°C to 280°C and 120°C to 290°C, respectively. Further heating beyond 260°C induced the highest thermal degradation rate which is reflected by the sharp weight reduction of the films.…”
Section: Thermal Stability Of the Filmsupporting
confidence: 88%
“…The thermal, mechanical and barrier properties of nanocomposite materials, which determined their suitability for packaging application, have been studied [6,[11][12][13][14][15][16]. Zeng et al [11], Taghizadeh and Sabouri [12] reported that the platelet nature of the nanoparticles usually hinders the diffusion of gases and specifically contributes to the improvement of their thermal and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, films became stiffer and more compact, thereby improving thermal stability (Hoque et al 2011;Wu et al 2014). The increased thermal stability of nanocomposite films might be due to the thermal resistance of Cloisite Na + and the nanodispersion of montmorillonite sheets in the polymer matrix (Zheng et al 2002). Martucci and Ruseckaite (2010a) reported the increased thermal stabilisation of gelatin nanocomposite films.…”
Section: Tga Thermogramsmentioning
confidence: 99%
“…By fitting permeation data to various phenomenological models, the aspect ratio can be estimated. [8][9][10] The aim of this study was to investigate the influence of relative humidity on the water vapor permeability of chitosan and the effect of nanofiller content on the water vapor and oxygen permeabilities of the chitosan nanocomposite films. Furthermore, the experimental permeability data was fitted to various permeability models.…”
Section: Introductionmentioning
confidence: 99%